Growing home dialysis: The Ontario Renal Network Home Dialysis Initiative 2012–2019. Issue 5 (September 2021) - Blake, Peter G; McCormick, Brendan B; Taji, Leena; Jung, James KH; Ip, Jane; Gingras, Joanie; Boll, Phil; McFarlane, Phil; Pierratos, Andreas; Aziz, Anas; Yeung, Angie; Patel, Monisha; et al.
The Ontario Renal Network (ORN), a provincial government agency in Ontario, Canada, launched an initiative in 2012 to increase home dialysis use province-wide. The initiative included a new modality-based funding formula, a standard mandatory informatics system, targets for prevalent home dialysis rates, the development of a 'network' of renal programmes with commitment to home dialysis and a culture of accountability with frequent meetings between ORN and each renal programme leadership to review their results. It also included funding of home dialysis coordinators, encouragement and funding of assisted peritoneal dialysis (PD), and support for catheter insertion and urgent start PD. Between 2012 and 2017, home dialysis use rose from 21.9% to 26.5% and then between 2017 and 2019 stabilised at 26% to 26.5%. Over 7 years, the absolute number of people on home dialysis increased 40% from 2222 to 3105, while the number on facility haemodialysis grew 11% from 7935 to 8767. PD prevalence rose from 16.6% to 20.9%, a relative increase of 25%. The initiative showed that a sustained multifaceted approach can increase home dialysis utilisation. Graphical Abstract This is a visual representation of the abstract.